Induction chemotherapy followed by intensity‐modulated radiotherapy versus concurrent chemoradiotherapy in nasopharyngeal carcinoma: A retrospective analysis. (5th April 2021) - He, Yan; Zhao, Zhihao; Wang, Ying; He, Jialing; Chai, Jiamin; Wei, Zhigong; Guan, Hui; Wang, Jingjing; Liu, Zheran; Li, Ruidan; Mu, Xiaoli; He, Ling; et al.
Abstract: Objectives: The optimal treatment strategy of combining systemic chemotherapy and radiotherapy for nasopharyngeal carcinoma (NPC) is controversial. This study aimed to compare the efficacy and toxicities of induction chemotherapy followed by intensity‐modulated radiotherapy (IC‐RT) versus concurrent chemoradiotherapy (CCRT) in NPC. Methods: Of 448 stage II‐IVb NPC patients treated with IC‐RT or CCRT were retrospectively analysed. The primary outcome was overall survival, which was analysed by using Kaplan‐Meier curves and log‐rank (Mantel‐Cox) test. Results: The median follow‐up was 66 months (interquartile range, 46‐84 months). There was no statistically significant difference in the estimated 5‐year overall survival (OS), progression‐free survival (PFS), distance metastasis‐free survival (DMFS) and locoregional relapse‐free survival (LRFS) between IC‐RT group and CCRT group (OS: 89.5% vs 91.7%, P = .568; PFS: 85.2% vs 87.5%, P = .615; DMFS: 90.9% vs 91.7%, P = .847; LRFS: 92.0% vs 96.9%, P = .104). In the multivariate analysis, the treatment group (IC‐RT vs CCRT) was not an independent prognostic factor for OS, PFS, DMFS and LRFS. Less advanced tumour stage and lymph node stage were predictive of higher OS. EBV‐DNA level was an independent prognostic factor that was only significantly associated with LRFS. Conclusions: IC‐RT achieves similar survival outcomes and treatment‐related toxicities as CCRT in OS, PFS, DMFS and LRFS for patients with NPC. We need multicentre randomised controlled trials to reconfirm our data.